Nutritional quality of giant kelp declines due to warming ocean temperatures. Issue 7 (26th October 2021) - Lowman, Heili E.; Emery, Kyle A.; Dugan, Jenifer E.; Miller, Robert J.
Abstract : Giant kelp Macrocystis pyrifera forms extensive forests on temperate reefs, providing habitat and food for a diversity of marine life. Kelp biomass varies in response to changing ocean temperatures, but physiological responses as reflected in the nutritional quality of kelp tissue are poorly understood. Over a 19‐year period in southern California, we found that nutritional quality of giant kelp tissue declined; nitrogen content of giant kelp tissue declined by 18%, while carbon content proportionally increased. This decline in nutritional quality was associated with increasing seawater temperatures and with regional and local scale processes including upwelling as indicated by the biologically effective upwelling transport index, the El Niño‐Southern oscillation and the North Pacific Gyre oscillation. Changes in kelp stoichiometry with seawater temperature have important implications for nutrition and behavior of key consumers, such as sea urchins. Our results suggest that the consequences of projected declines in kelp abundance due to climate change may be compounded by reductions in its nutritional quality.